Penerapan Metode Demontrasi untuk Meningkatkan Hasil Belajar IPA pada Materi Teori Dasar Kemagnetan di SMP Negeri 1 Krangkeng Kabupaten Indramayu - N. Iin Rumsinah (Jurnal Pendidikan Madrasah, 2023)
This research aims to improve science learning outcomes on solar system materials. The research subjects are grade IX A SMP Negeri 1 Krangkeng students of Indramayu Regency for the 2021/2022 academic year with a total of 30 students. The method used is a demonstration method, so that students more easily understand and practice what they get. This study is a classroom action research, consisting of two cycles. Data was collected using test question items and student activity instrument sheets. Data validation is carried out by entering test scores into the list of scores along with the results of observations of student activities during learning. Data analysis techniques use percentage descriptive statistics. The research procedure includes the stages, namely planning, implementation, observation and reflection. The results showed that there was an increase in student learning completeness, from 65% in cycle I, increasing to 90% in cycle II.